The role of membrane destabilisation and protein dynamics in BAM catalysed OMP folding - Paul White (Nature Portfolio, 2021)
The folding of outer membrane proteins (OMPs) is catalyzed by the βbarrel assembly machinery (BAM). Here, structural and functional analyses of BAM stabilized in distinct conformations elucidate the roles of lateral gate opening and interactions of BAM with the lipid bilayer in OMP assembly.